Analysis of the Relationship between Laboratory Biomarkers and the Severity of COVID-19 at Kaliwates General Hospital Jember - Nadzir Ansharullah Akbar; Angga Mardro Rahardjo; Dita Diana Parti; Elly Nurus Sakinah (Journal of Agromedicine and Medical Sciences, 2022)
Coronavirus Disease 2019 (COVID-19) has become a global health problem since the WHO declared the disease a pandemic. In July 2021, Indonesia experienced a very sharp spike in cases and an increase in mortality due to COVID-19, including at the Kaliwates General Hospital in Jember. Laboratory biomarkers in the form of Neutrophile Lymphpocyte Ratio (NLR), D-dimer, and SpO2 can be a clue to assess the severity of COVID-19 patients. This research is an observational analytical study using a Cross Sectional Study with the aim of knowing the relationship between laboratory biomarkers and the severity of COVID 19 at RSU Kaliwates Jember. This study uses secondary data in the form of medical records of COVID-19 patients during July 2021 with a total of 50 samples. The results of this study were carried out by the Spearman correlation test and it was found that there was a correlation between NLR values ​​and oxygen saturation with the severity of COVID-19, but there was no relationship between D-dimer levels and the severity of COVID-19. The conclusion of this study is that NLR biomarkers and oxygen saturation can be used as predictors of the severity of COVID-19.